Integrated GIS-AHP Optimization For Bioethanol From Oil Palm Biomass Supply Chain Network Design - Razak, Nurul Hanim; Hashim, Haslenda; Yunus, Nor Alafiza; Klemeš, Jiří Jaromír (Italian Association of Chemical Engineering (AIDIC), 2021)
Integrated GIS-AHP network design optimization models via LP is proposed to solve the bi-objective biomass supply chain optimization problems inclusive of the management of cost-effective biomass resourcing spatial availability, optimal sites of biorefinery, and transportation network. The formulation is modeled through LP to minimize the logistic costs and GHG emissions. The case study focused on 78 palm oil plantations in Johor. The optimal biorefinery size and location were found by minimizing the total logistic cost by having less travel distance. The network design analysis feature in ArcMap is adopted in the analysis of the road transportation network by utilizing the ‘OD cost matrix’ function. This spatial analysis is employed to calculate distances between supply nodes, biorefinery nodes, and demand nodes. There are about 8/78 resource locations and only a biorefinery has been selected with a total logistic 1.1 M USD/y and total GHG emissions about 0.128 Mt CO2/y